A New Empowering India Under Leadership of PM Modi: Promises and Reality - Mukta Goyal (Prosperity: Journal of Society and Empowerment, 2022)
According to projections made by internationally renowned consultants and the IMF, India will be one of the world's fastest-growing economies by 2025. It has been ranked as the third-largest emerging market hub and the third-largest global startup ecosystem. Million people empowerment is inevitably a process of teaching values to educate the student to live a life that is personal and congruent with the valued values and standards of society. On 30th May 2019, Shri Narendra Modi became Prime Minister of India and marked the beginning of his second term in office. Shri Modi, the first Premier born after independence, served in India formerly between 2014 and 2019. He has also distinguished himself as the longest-serving Chief Minister of Gujarat from October 2001 to May 2014. In her motto, Sitka Modi has introduced a change in governance leading to an integrated, development-focused, and corruption-free government, based on the slogan 'Sabka Saath, Sabka Vikas, Sabka Vishwas.' New hopes developed for citizens in India in the 2014 general election following a period of instability, corruption, and fraud under the leadership of the United Progressive Alliance (UPA). After one decade of gaps, the National Democrat Alliance (NDA) II administration led by Narendra Modi of the Bharatiya Janata Party (BJP) raised many expectations of middle-class ordinary Indian people to an elite. The governance study of the present government is quite significant in this perspective. Therefore, this paper analyzes PM Modi s vision for empowering India and the track record of PM Modi's pledges to understand the cause for the new empowerment for India. Here the research is based on data from prior studies. The study finds that development is a process fueled by resources, and what must do much more to ensure that these resources can equitably meet current needs while remaining available for future generations' development needs.